Toxicidade e atividade tripanocida do extrato bruto de Brosimum gaudichaudii trécul (Moraceae) (Mama-cadela) no pré-tratamento e tratamento de camundongos infectados por Trypanosoma cruzi - Ferreira, Paulo Cesar (2008)
The objective of this work was to evaluate the toxicity and the trypanocidal activity of Brosimum gaudichaudii Trécul (Moraceae) crude extract, also knowed as mamacadela , in pre-treatment and treatment of mice infected by Trypanosoma cruzi. For the pretreatment, the animals received 100 mg/kg of B. gaudichaudii crude extract starting in three different moments: 7days (GBg7), 3 days (GBg3) and 1 day (GBg1) before infection. For the treatment, animals were given, after infection, different quantities of B. gaudichaudii crude extract: G100 (100 mg/kg), G200 (200 mg/kg) and G400 (400 mg/kg). In both cases there was a control group composed by animals submitted to the same stress conditions, but treated with water only. The toxicity assays carried out were DL50 test (in vivo) and the Artemia salina bioassay (in vitro). On both toxicity assays, the crude extract do not demonstrated statistically significant results for toxicity. On the experimental treatment, a positive result occurred on group G100 (100 mg/kg) where the reduction on parasitemia was about 30%. On the pre-treatment, the results showed that in experimental conditions, the B. gaudichaudii crude extract delayed the parasitemia and reduced its intensity on GBg1 (reduction of 50%), GBg3 (reduction of 12%) and GBg7 (reduction of 73%) groups. Based on these results, it is possible to conclude that the B. gaudichaudii crude extract do not present acute toxic activity and contain components capable to interfere on T. cruzi infection in mice pre-treated and treated with it.